Single-pass transformation of syngas into ethanol with high selectivity by triple tandem catalysis - Kang, Jincan; He, Shun; Zhou, Wei; Shen, Zheng; Li, Yangyang; Chen, Mingshu; Zhang, Qinghong; Wang, Ye (Nature communications, 2020)
Synthesis of ethanol from non-petroleum carbon resources via syngas (a mixture of H 2 and CO) is an important but challenging research target. The current conversion of syngas to ethanol suffers from low selectivity or multiple processes with high energy consumption. Here, we report a high-selective conversion of syngas into ethanol by a triple tandem catalysis. An efficient trifunctional tandem system composed of potassium-modified ZnO–ZrO 2 , modified zeolite mordenite and Pt–Sn/SiC working compatibly in syngas stream in one reactor can afford ethanol with a selectivity of 90%. We demonstrate that the K + –ZnO–ZrO 2 catalyses syngas conversion to methanol and the mordenite with eight-membered ring channels functions for methanol carbonylation to acetic acid, which is then hydrogenated to ethanol over the Pt–Sn/SiC catalyst. The present work offers an effective methodology leading to high selective conversion by decoupling a single-catalyst-based complicated and uncontrollable reaction into well-controlled multi-steps in tandem in one reactor. Direct synthesis of ethanol from non-petroleum carbon resources via syngas (CO/H 2 ) is a highly attractive but challenging target. Here, the authors report a triple tandem catalytic system for single-pass conversion of syngas into ethanol with selectivity as high as 90%.